Studies Of Capability, Stability, Toxicity And Bioefficacy Of Kenaf Based Cellulose Nanofiber As Larvicide Carrier For Mosquito Control - Pengiran, Hazirah (2022)
Mosquito-borne diseases are increasing every year and causing million deaths worldwide. The diseases are transmitted from the bite of an infected mosquito. Thus, it requires effective control measures to reduce the transmission rate, and one of the control strategies is using larvicide such as temephos. Currently, the carrier materials used in the larvicide formulation raised environmental concerns due to their nonrenewable sources. The cellulose nanofiber from kenaf is seen as a sustainable replacement for larvicide carrier. The objectives of this study are to determine the capability of kenaf cellulose nanofiber (KCNF) to disperse and load temephos, the stability of KCNF impregnated with temephos (KCNF+T) in retaining temephos, the acute systemic toxicity of KCNF and KNCF+T in mammals, the acute ecotoxicity of KCNF in the aquatic organisms and the bioefficacy of KCNF+T as a larvicide carrier against Aedes aegypti mosquito larvae. The capability of KCNF to disperse is determined using the method adopted from OECD TG 318 and loading capability is evaluated using various water volume loaded on the dry KCNF. The amount of temephos impregnated on KCNF is quantified by HPLC analysis. KCNF is found to have high dispersion capability with more than 50 % dispersibility in six out of nine tested hydrochemical conditions and loading capability 6-fold of its mass. Amount of temephos impregnated on KCNF is found 1.94 % w/w reflecting 97 % impregnation efficacy.